Tari Pajoge dan Nilainya dalam Perspektif Akuntansi Budaya Bugis Bone - Akbar Aprian. H; Rohana Rohana; Muhammad Yamin; Ulfa Sari; Ganim Mohammed Mosa Mohammed; Eslam Amir Mohammed (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the character and cultural meaning of the Pajoge Dance within the Bugis community and analyzes its economic value through the perspective of cultural accounting. A qualitative descriptive-interpretive approach was employed using interviews, documentation, and literature review, with data analyzed through an interactive model involving data reduction, presentation, and conclusion drawing. The findings reveal that the Pajoge Dance embodies values of respect, politeness, social harmony, and cultural identity through symbolic movements such as mappakaraja, mappasompe, ballung, and massimang. From a cultural accounting perspective, the dance generates economic value through performance service income, voluntary mappasompe contributions, and the distribution of financial benefits among dancers, musicians, and supporting participants. The performances also stimulate local economic activities by creating income opportunities for providers of transportation, costumes, equipment, and other supporting services, producing a multiplier effect within the cultural economy. These findings demonstrate that the Pajoge Dance functions as both a cultural heritage asset and a sustainable source of community-based economic value.